2010
DOI: 10.1111/j.1530-0277.2010.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Alcohol Exposure Impair the Phagocytosis of Apoptotic Cells and Enhance the Pulmonary Inflammatory Response

Abstract: Background-Alcohol abuse increases the risk for acute respiratory distress syndrome (ARDS). Efferocytosis, the clearance of apoptotic cells, is important in the resolution of inflammation and is regulated by RhoA and rho kinase (ROCK) activation. The effects of alcohol on pulmonary Rho pathway activation and efferocytosis have not been determined. We hypothesize that acute and chronic alcohol exposure impair pulmonary efferocytosis, leading to heightened inflammation during ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 52 publications
4
29
0
Order By: Relevance
“…Previous studies have shown that acute alcohol exposure attenuates macrophage efferocytosis (13). However, the exact molecular mechanisms underlying the effect remain largely unknown.…”
Section: Downregulation Of Mfg-e8 Gene Expression Is An Underlyingmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that acute alcohol exposure attenuates macrophage efferocytosis (13). However, the exact molecular mechanisms underlying the effect remain largely unknown.…”
Section: Downregulation Of Mfg-e8 Gene Expression Is An Underlyingmentioning
confidence: 99%
“…Recently, Boé et al demonstrated that alcohol exposure results in impairment of efferocytosis, a process with characteristics that are distinct from engulfment of microorganisms (13). The effect of alcohol on inhibiting efferocytosis is partially mediated by RhoA-independent activation of ROCK (13). However, it remains unclear whether alcohol targets bridging molecules and subsequently disrupts efferocytosis.…”
Section: Mfg-e8 and Hmgb1 Are Involved In The Mechanism Underlying Almentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased immune functions associated with chronic alcohol consumption include granulopoiesis (8), tissue recruitment of neutrophils (9), TLR responsiveness of macrophages (10), and production of IL-12 (11). In addition, decreased macrophage phagocytosis (12)(13)(14) and an increased Th2 response (11,15,16) were demonstrated in alcoholics. A decrease in the Ag-presenting abilities of dendritic cells (17), perforin/granzyme expression, IFN-g production by conventional NK cells (18,19), and Th1/Th17 responses (20)(21)(22) also were reported.…”
Section: Cd14mentioning
confidence: 99%
“…Because such infections do not usually develop in healthy individuals, certain immune dysfunctions related to alcohol abuse are considered the underlying causes of the increased susceptibility of alcoholics to these infections. In fact, various host antibacterial immune functions are strongly influenced by chronic alcohol consumption (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Decreased immune functions associated with chronic alcohol consumption include granulopoiesis (8), tissue recruitment of neutrophils (9), TLR responsiveness of macrophages (10), and production of IL-12 (11).…”
Section: Cd14mentioning
confidence: 99%